The Loss of Tawhidi Worldview in Islamic World: Another Ecological Consequence of Modernization - Alkatiri, Wardah (Comparative Islamic Studies, 2021)
Modernization and the concomitant changes in people behavior are now blamed for the deterioration of the environment. This article points up desacralization of knowledge and the demise of esoteric tradition that followed to have an ecological impact in the Islamic world as the Muslims began to hold the bifurcated notion of “this-worldly” and “heavenly” in a completely distinct manner. Through modern education, Muslims adopted the notion of “independent existence” according to which nature exists in and of itself. Hence, the modernist vision of development and progress that threw the life-support system of the earth out of balance was possible in the Islamic world where religion and its cultural traditions remained strong. The twentieth century’s awareness about the need of an integrative framework to reconcile rational thought and science with a spiritual sense of awe for the cosmos, should remind the Muslims of the unitive worldview that arise from the core of Islamic belief—tawhid—expounded by esoteric Islam. Further, this article argues that science needs to repossess a metaphysical foundation, and that ethics and values need to be reintegrated into our rationality. Three case studies reveal mental crises caused by an overweening trust in science. I use data from my own extreme life experience, and biographical data suggestive of existential depression of two arguably highly gifted individuals. Drawing upon the data, the article juxtaposes the “unitive worldview” associated with mystical experience and the “evolutionary worldview” given rise by Darwin’s evolutionary biology, to put forward an examination of the effects that worldviews might have on human minds. The analysis adopts organic inquiry within transpersonal psychology research method, and content analysis of biographical data. Designed to investigate the “non-objective” spiritual reality, organic inquiry offers a rigorous method for those attempting to incorporate spiritual experience and mysticism into academic work. As a whole, the case studies present an example of the biologization of ethics; discusses social Darwinism and giftedness phenomena; and explicate the unitive worldview granted by mystical experiences.